Relationship of Noise Intensity, Heat Stress, and Physical Workload to Workers' Health Complaints at Semarang Timber Factory - Bian Ganda Atmaja; Yuliani Setyaningsih; Ida Wahyuni (Disease Prevention and Public Health Journal, 2022)
Background: As a country with a developed industry, the majority of entrepreneurs in Indonesia use modern industrial tools to help make their work easier. However, using modern technology causes side effects, such as noise from machines that cause hearing complaints. In addition, the hot work environment causes discomfort during work, and the excessive physical workload makes workers experience health complaints. Methods: This quantitative research uses a cross-sectional study approach with a purposive sampling technique. The sample consisted of 60 workers from a total of 126 in a wood factory in Semarang. The research instrument is a health complaint questionnaire sheet and a noise (a sound level meter), a physical workload (an oximeter), and a heat pressure (the QUESTemp). Data was analyzed by univariate and bivariate using the chi-square test. Results: The highest noise intensity is 98.02 dB, the highest heat pressure is 33.4°C, and the majority of the physical workload felt by workers is in the medium category. The chi-square test shows a relationship between noise intensity, heat stress, and health complaints of workers in a Semarang wood factory (p<0.05). Meanwhile, physical workload has no relationship with the health complaints of workers at the Semarang wood factory (p>0.05). Conclusion: Semarang wood factory has noise intensity and heat stress exceeding the threshold value, and most workers experience moderate physical workloads. The company should direct control of workers through the use of personal protective equipment and adequate drinking water, as well as controlling physical workloads on workers with workplace stretching exercises.